The artistic journey of Zainon Abdullah / Mahizan Hijaz Mohammad - Mohammad, Mahizan Hijaz (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
The fine arts programme and the committee of the gallery of al Biruni FSSR Perak were delighted to host the solo exhibition by a renowned artist and a senior lecturer of the faculty of art and design (fssr), Zainon Abdullah, entitled "perjalanan" (the journey). This historical event was also partly organized by bachelor (hons) of fine arts final semester students, as a part of their art curatorial course project.